The Role of Crowdfunding in Fostering Entrepreneurship and Catalyzing Investment: A National Platform Model for Supporting Startups in Iraq - Laith Haleem Al-Hchemi (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This research aims to explore the possibility of using crowdfunding as a tool to promote entrepreneurship and investment in Iraq by presenting a national platform model that combines private funding and government support. The research looks into the ability of crowdfunding to transform unused savings in banking channels into productive investments that support projects, raise investment awareness and reduce unemployment rates. The research highlights the structural challenges of the Iraqi economy including weak digital infrastructure, absence of regulatory and legislative frameworks and low trust between citizens and financial and banking institutions. The study used a critical analytical methodology combining literature review and analysis of international successful experiences based on quantitative and qualitative data and a review of the most famous global crowdfunding platforms. The results showed that crowdfunding provides flexible financing options for emerging projects, investment and financial inclusion and the importance of the proposed model as a development tool. Therefore the research recommends to adopt this model as a solution to the current economic problems. Keywords: Crowdfunding; Entrepreneurship; Investment; Digital Transformation; Fintech